Plutarco, Narrazioni d'amore, intr., trad., e commento a cura di G. Giangrande, Napoli, M. D'Auria Editore, 1991, 89 pp. ISBN 88-7092-079-8 (Minerva, 2019)
Review: Plutarco, Narrazioni d'amore, intr., trad., e commento a cura di G. Giangrande, Napoli, M. D'Auria Editore, 1991, 89 pp. ISBN 88-7092-079-8